Activity profiles of elite wheelchair rugby players during competition - Rhodes, James M.; Mason, Barry S.; Perrat, Bertrand; Smith, Martin J.; Malone, Laurie A.; Goosey-Tolfrey, Victoria L. (Human Kinetics, 2015)
To quantify the activity profiles of elite wheelchair rugby and establish classification-specific arbitrary speed zones. Additionally, indicators of fatigue during full matches were explored. Methods: Seventy-five elite wheelchair rugby players from eleven national teams were monitored using a radio-frequency based, indoor tracking system across two international tournaments. Players who participated in complete quarters (n = 75) and full matches (n = 25) were included and grouped by their International Wheelchair Rugby Federation functional classification: group I (0-0.5), II (1.0-1.5), III (2.0-2.5) and IV (3.0-3.5). Results: During a typical quarter, significant increases in total distance (m), relative distance (m·minˉ¹), and mean speed (m·sˉ¹) were associated with an increase in classification group (P < 0.001), with the exception of group III and IV. However, group IV players achieved significantly higher peak speeds (3.82 ± 0.31 m·sˉ¹) than groups I (2.99 ± 0.28 m·sˉ¹), II (3.44 ± 0.26 m·sˉ¹) and III (3.67 ± 0.32 m·sˉ¹). Groups I and II differed significantly in match intensity during very low/low speed zones and the number of high-intensity activities in comparison with groups III and IV (P < 0.001). Full match analysis revealed that activity profiles did not differ significantly between quarters. Conclusions: Notable differences in the volume of activity were displayed across the functional classification groups. However, the specific on-court requirements of defensive (I and II) and offensive (III and IV) match roles appeared to influence the intensity of match activities and consequently training prescription should be structured accordingly.